EFISIENSI DAN EFEKTIVITAS PELAYANAN RUMAH SAKIT SETELAH PEMEKARAN WILAYAH - Putra, Windhu (Universitas Negeri Semarang, 2012)
This study aims to identify the efficiency of health services districts / cities before and after the regional proliferation, understand the indicators that affect the change in efficiency and to design a health cooperative district / town after the regional proliferation. It was conducted in 9 districts; Pontianak, Sambas, Sanggau, Sintang, Singkawang, Bengkayang, Landak, Sekadau, Melawi. Data Envelopment Analysis is used to calculate the efficiency at each hospital in the parent division area and regional levels. this study also uses rationality of resource efficiency analysis.The result first, a change in the efficiency of health services after the introduction of regional proliferation. It causes declining health of economies of scale; Second, the seven indicators of input factors; General Practitioners, Specialists, Pharmacists, Nurses , Employees, Total polyclinic, and the Investment Fund for hospital, which most influence the change in efficiency is a specialist doctor, nurse and the number of polyclinics. They influence the level of efficiency. Third, In implementing the policy of expansion, which related to health care services, need designed a model hospital revitalisai by considering the number of specialist doctors, nurses and polyclinics. The combination of these factors, will greatly affect the model of health care in the profilferation area.Â Penelitian ini lebih diarahkan kepada upaya merevitalisasi kondisi daerah pemekaran melalui kerjasama di bidang kesehatan agar terjadi bentuk kerjasama yang efisien berdasarkan keunggulan aspek kesehatan yang ada pada masing-masing daerah. Penelitian ini mengidentifikasi efisiensi pelayanan kesehatan kabupaten/kota sebelum dan sesudah pemekaran wilayah. Lokasi Penelitian berada di 9 daerah kabupaten yang terdiri dari 4 kabupaten daerah induk, yaitu; Kabupaten Pontianak, Kabupaten Sambas, Kabupaten Sanggau, Kabupaten Sintang. Serta 5 kabupaten daerah pemekaran, yaitu ; Kota Singkawang, Kabupaten Bengkayang, Kabupaten Landak, Kabupaten Sekadau, Kabupaten Melawi. Metode analisis yang digunakan adalah dengan Data Envelopment Analysis (DEA) untuk menghitung efisiensi pada setiap rumah sakit di daerah pemekaran maupun daerah induk. Selain itu penelitian ini juga menggunakan analisis efisiensi rasionalitas sumber daya dalam membentuktata kelola kerjasama kesehatan antara kabupaten.